Paralasianthus (Rubiaceae), a new genus from Southeast Asia - Hua, Zhu (Phytotaxa, 2015)
The new genus Paralasianthus is described from South-East Asia. Five species are recognised in the genus, four of which required new combinations, P. brevipes, P. dichotomus, P. lowianus and P. hainanensis, and one is described as a new species, P. zhengyianus. A key to the species is presented.